2021
DOI: 10.1016/j.gca.2021.05.056
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of basalt–seawater–CO2 interaction at 130 °C

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 81 publications
3
21
0
1
Order By: Relevance
“…In the NAIP, the last erupted sequences of the province which were buried in the sub-surface before the extensive erosion that has stripped off the youngest and least altered intervals of the Faroe Islands Basalt Group may therefore contain the best reservoirs for CO 2 storage. The results presented herein support existing evidence that basaltic rocks provide good sources of divalent metal cations for potential carbonate precipitation (Gudbrandsson et al, 2011;Kelemen et al, 2019;Matter et al, 2016;Pogge von Strandmann et al, 2019), which can also occur in systems where seawater is the reservoir fluid (Voigt et al, 2021).…”
Section: Applications For Co 2 Storagesupporting
confidence: 86%
See 2 more Smart Citations
“…In the NAIP, the last erupted sequences of the province which were buried in the sub-surface before the extensive erosion that has stripped off the youngest and least altered intervals of the Faroe Islands Basalt Group may therefore contain the best reservoirs for CO 2 storage. The results presented herein support existing evidence that basaltic rocks provide good sources of divalent metal cations for potential carbonate precipitation (Gudbrandsson et al, 2011;Kelemen et al, 2019;Matter et al, 2016;Pogge von Strandmann et al, 2019), which can also occur in systems where seawater is the reservoir fluid (Voigt et al, 2021).…”
Section: Applications For Co 2 Storagesupporting
confidence: 86%
“…The comparison between the divalent metal cations indicates that Ca 2+ is the dominant cation released during the dissolution of the Faroe Islands rocks. The release rate of divalent metal cations would control the type of carbonate mineral precipitation during CO 2 storage and suggests that calcite or aragonite precipitation would be favoured, depending on the chemical and physical conditions (e.g., Gysi and Stefánsson, 2008;Tutolo et al, 2021;Voigt et al, 2021). This study has found the relative mobility of Ca during the dissolution of each sample to show an inverse relationship to the overall rock dissolution rates (i.e., Si release rates).…”
Section: Basalt and Sediment Reactivitymentioning
confidence: 68%
See 1 more Smart Citation
“…The list of Orange hydrogen advantages does not end here. In contrast to electrolysis, where only specically tuned water compositions can be used, natural oxidation of iron as well as carbon mineralization works very well with seawater [29] or even wastewater, alleviating signicantly the water cost of hydrogen production. Target formations can also contain elements of economic interest such as Li, Ni, Co. .…”
Section: Orange Hydrogenmentioning
confidence: 99%
“…Mais dans d'autres systèmes, la disponibilité en eau douce pourrait représenter un obstacle. Une étude récente suggère cependant qu'il serait possible d'obtenir des taux de minéralisation comparables à ceux observés dans le cadre du projet CarbFix en utilisant de l'eau de mer à la place de l'eau douce (Voigt et al, 2021), ce qui laisse entrevoir tout le potentiel sous-marin de la minéralisation.…”
Section: Deux Projets Pilotesunclassified